Próba identyfikacji zasięgu oddziaływania lodowca górskiego na temperaturę powietrza - na przykładzie lodowca Engabreen (Norwegia) - Dyszy, Wiktoria; Grajek, Zofia (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
This study aims to identify the extent of mountain glacier influence on air temperature in the vertical profile, using the Engabreen glacier (Norway) as an example. An important aspect of the work is also an analysis of the variation in surface temperature and wind conditions in the valley of the Engabreen glacier. The analysis was carried out based on measurement data of vertical air temperature taken over the glacier cavity with sensors mounted to an unmanned aerial vehicle. The field survey was carried out on 25 July 2022 in the afternoon. The results of the measurements may indicate that the presence of the glacier reduces the air temperature gradient with altitude compared to the surrounding areas. Above the glacier, the air temperature in the vertical profile increases with height. Based on the profiles taken above the glacier, it was concluded that the surface of the glacier influences the air temperature above it up to an altitude of 37–53 m above ground level.